2017
DOI: 10.1002/hlca.201700082
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N‐alkyl‐N′‐aryl or Alkenylpiperazines: A Copper‐Catalyzed C–N Cross‐Coupling in the Presence of Aryl and Alkenyl Triflates and DABCO

Abstract: Unsymmetrical piperazines are key constituents of many pharmaceuticals. Given that the selective introduction of an aryl and alkyl motif onto the piperazine is not always straightforward, direct arylation and alkenylation of 1,4‐diaza‐bicyclo[2.2.2]octane would obviate the inefficiencies associated with the preparation of these target molecules. We have utilized alkyl halides, aryl or alkenyl triflates, and 1,4‐diaza‐bicyclo[2.2.2]octane for the synthesis of N‐alkyl‐N′‐aryl or alkenylpiperazines. The optimum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In addition, the synthesis of unsymmetrical piperazines with the same strategy is further developed by Ghazanfarpour-Darjani and coworkers. 43 They have utilized alkyl chlorides, DABCO ring opening reaction (Scheme 30). 44 Diversely substituted pyridine N-oxides, quinolone-N-oxides, and 1,10phenanthroline 1-oxide were applied successfully in this protocol.…”
Section: Transition-metal Catalyzed Dabco Bond Cleavagementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the synthesis of unsymmetrical piperazines with the same strategy is further developed by Ghazanfarpour-Darjani and coworkers. 43 They have utilized alkyl chlorides, DABCO ring opening reaction (Scheme 30). 44 Diversely substituted pyridine N-oxides, quinolone-N-oxides, and 1,10phenanthroline 1-oxide were applied successfully in this protocol.…”
Section: Transition-metal Catalyzed Dabco Bond Cleavagementioning
confidence: 99%
“…In addition, the synthesis of unsymmetrical piperazines with the same strategy is further developed by Ghazanfarpour-Darjani and coworkers. 43 They have utilized alkyl chlorides, aryl(heteroaryl) triflates and DABCO under optimal reaction conditions [CuCl (5 mol%), t -BuOLi (1.5 equiv. ), and NMP as solvent at 70 °C for 14 h] to provide N -alkyl- N ′-aryl (heteroaryl) piperazines 78 in 73–93% yields.…”
Section: Transition-metal Catalyzed Dabco Bond Cleavagementioning
confidence: 99%
“…We have previously reported that covalently coupling a four-carbon chain linker and a moiety capable of binding a secondary binding site (SBS) (also referred to as an allosteric site) to phenyl­piperazine analogs modulates their affinity and selectivity for the D2R and D3R subtypes. Furthermore, we also found that the addition of a phenyl­thiophene moiety generates D3R vs D2R selective ligands that bind with high affinity to the D3R. Previous studies suggested that the SBS is located in the extracellular loops (ECL) of the D3R. , In contrast, coupling the phenyl­piperazine with the linker and 4-dihydro-2­(1 H )-quinolinone causes the compounds to be D2R selective, which is not desirable for therapeutic purposes . In this manuscript, we further investigate how compounds that either lack or contain an allosteric fragment interact at the D2R and D3R subtypes using both experimental and computational approaches.…”
Section: Introductionmentioning
confidence: 98%